Metrics, Accentual Rhyhm, and Authorship in Golden Age Spanish Poetry - Llamas Martínez, Jacobo (Arte Nuevo. Revista de Estudios Áureos, 2018)
Introduction to the dossier «Metrics, Accentual Rhythm, and Authorship in Golden Age Spanish Poetry» and connection of this dossier to a congress stemming from an on-going research project.